2015
DOI: 10.1371/journal.pone.0121980
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Repair-Deficient Crypt Foci in Lynch Syndrome – Molecular Alterations and Association with Clinical Parameters

Abstract: Lynch syndrome is caused by germline mutations of DNA mismatch repair (MMR) genes, most frequently MLH1 and MSH2. Recently, MMR-deficient crypt foci (MMR-DCF) have been identified as a novel lesion which occurs at high frequency in the intestinal mucosa from Lynch syndrome mutation carriers, but very rarely progress to cancer. To shed light on molecular alterations and clinical associations of MMR-DCF, we systematically searched the intestinal mucosa from Lynch syndrome patients for MMR-DCF by immunohistochemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 38 publications
3
74
3
Order By: Relevance
“…A recent study showed that the number of MMR-deficient crypt foci in the colorectal epithelium increased with age. 29 Because adenomas arising from MMR-deficient crypt foci are expected to lack MMR protein expression consistently, this observation appears to provide a reasonable explanation for the correlation between the prevalence of MMR deficiency and patient age as well as for the absence of adenomas with focal loss of MMR proteins. We suggest that a significant proportion of LS-associated adenomas, particularly those in older patients, may arise from MMR-deficient crypt foci ( Figure 2).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A recent study showed that the number of MMR-deficient crypt foci in the colorectal epithelium increased with age. 29 Because adenomas arising from MMR-deficient crypt foci are expected to lack MMR protein expression consistently, this observation appears to provide a reasonable explanation for the correlation between the prevalence of MMR deficiency and patient age as well as for the absence of adenomas with focal loss of MMR proteins. We suggest that a significant proportion of LS-associated adenomas, particularly those in older patients, may arise from MMR-deficient crypt foci ( Figure 2).…”
Section: Discussionmentioning
confidence: 80%
“…Conversely, these findings seem to be well explained when considering tumorigenesis via MMR‐deficient crypt foci. A recent study showed that the number of MMR‐deficient crypt foci in the colorectal epithelium increased with age . Because adenomas arising from MMR‐deficient crypt foci are expected to lack MMR protein expression consistently, this observation appears to provide a reasonable explanation for the correlation between the prevalence of MMR deficiency and patient age as well as for the absence of adenomas with focal loss of MMR proteins.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the recurrent exposure of immune cells towards MSIrelated antigens in Lynch syndrome, e.g. through mismatch repair-deficient crypts 1,40,41 may lead to T cell activation and consequently an enhanced number of activated T cells in clinically manifest tumors. The recurrent stimulation of the immune system with MSIinduced FSP neoantigens in Lynch syndrome may thus be the reason for the higher frequency of B2M mutations in Lynch syndrome-associated compared to sporadic MSI colorectal cancers 42 This supports the concept that stimulating the immune system against MSI-related FSP antigens, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Losing the expression of MMR proteins via inactivation of MMRTezcan G et al . Molecular aspects of early-onset colorectal cancer deficient crypt foci genes causes an MSI phenotype [30] . In these patients, the mutation rates of ACVR2, TAF1B and ASTE1, microsatellite-bearing target genes are higher than 80% [29][30][31][32][33] .…”
Section: Lsmentioning
confidence: 99%
“…Molecular aspects of early-onset colorectal cancer deficient crypt foci genes causes an MSI phenotype [30] . In these patients, the mutation rates of ACVR2, TAF1B and ASTE1, microsatellite-bearing target genes are higher than 80% [29][30][31][32][33] . Recent studies indicated that in MSI cases, frameshift mutations of apoptotic genes, such as APAF1, BAX and FLASH, lead to intratumoral heterogeneity [28] .…”
Section: Lsmentioning
confidence: 99%